Microalgae biotechnology as an attempt for bioregenerative life support systems: problems and prospects. Issue 10 (12th August 2019) - Yang, Limin; Li, Huankai; Liu, Tonggui; Zhong, Yuqing; Ji, Chengcheng; Lu, Qian; Fan, Liangliang; Li, Jun; Leng, Lijian; Li, Kun; Zhou, Wenguang
ABSTRACT: Bioregenerative life support system (BLSS) plays a key role in the long‐duration manned space mission. Microalgae‐based BLSS was proposed decades ago but it had a variety of technical problems hindering its application in space mission. However, in recent years, a lot of effort has been devoted to this field and great progresses have been achieved in the research of microalgae‐based BLSS. Therefore, the main aim of this work is to summarize the previous progress and find the challenges faced by microalgae‐based BLSS technology. In this regard, this works introduces the concept of microalgae‐based BLSS and presents its development paths in the past decades. Additionally, technology updates in the aspects of microalgae‐based oxygen generation, value‐added biomass production as food alternative, and wastes treatment by microalgae are summarized. Challenges faced by microalgae‐based BLSS and potential solutions are discussed. This work provides a deep understanding of microalgae‐based BLSS and that it would be beneficial for promoting implementation of this novel technology in manned space missions. © 2019 Society of Chemical Industry